2013
DOI: 10.1371/journal.pone.0069997
|View full text |Cite
|
Sign up to set email alerts
|

Manipulation of the Porcine Epidemic Diarrhea Virus Genome Using Targeted RNA Recombination

Abstract: Porcine epidemic diarrhea virus (PEDV) causes severe economic losses in the swine industry in China and other Asian countries. Infection usually leads to an acute, often lethal diarrhea in piglets. Despite the impact of the disease, no system is yet available to manipulate the viral genome which has severely hampered research on this virus until today. We have established a reverse genetics system for PEDV based on targeted RNA recombination that allows the modification of the 3′-end of the viral genome, which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
74
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(77 citation statements)
references
References 31 publications
2
74
1
Order By: Relevance
“…In contrast to our results, they showed that disruption of ORF3 expression by small interfering RNA resulted in decreased virus production in infected Vero cells. However, the high growth of ORF3-null PEDV shown in this study and by Li et al (2013) disputes the essential role of ORF3 in PEDV replication. It is also worth pointing out that our results so far suggest a strong correlation between ORF3 and cell-culture adaptability.…”
contrasting
confidence: 67%
See 2 more Smart Citations
“…In contrast to our results, they showed that disruption of ORF3 expression by small interfering RNA resulted in decreased virus production in infected Vero cells. However, the high growth of ORF3-null PEDV shown in this study and by Li et al (2013) disputes the essential role of ORF3 in PEDV replication. It is also worth pointing out that our results so far suggest a strong correlation between ORF3 and cell-culture adaptability.…”
contrasting
confidence: 67%
“…However, the recovery of infectious PEDV using the full-length cDNA approach has been challenged by several technical difficulties, one of which is the fact that available cell lines do not adequately support productive replication of the virus, and the full-length cDNA clone of PEDV is not stable in conventionally used plasmid vectors. Notably, Li et al (2013) recently described the reverse genetics of PEDV based on targeted RNA recombination technology. Although applicable, this approach could be complicated by several steps including the generation of a PEDV derivative carrying spikes derived from another coronavirus, and use the RNA of this so-called chimeric virus as an intermediate for recombination with a parental RNA to restore the PEDV spike.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, how the sialic acid binding activity affects the tropism of these alphacoronaviruses remains unclear. The S protein N-domain of some PEDV strains were thought to be dispensable for replication of PEDV in vitro [4446]. The large deletions in the S protein of the PEDV variants in this study indicated that this domain might also be dispensable in vivo .…”
Section: Resultsmentioning
confidence: 69%
“…Reverse genetics systems are valuable tools to study the functions of viral genes and to generate recombinant viruses with defined genetic changes as vaccine candidates. In 2013, Li et al first reported a reverse genetics system for the Korean classical PEDV vaccine strain DR13 based on a targeted RNA recombination method (Li et al, 2013). Following this, Jengarn et al engineered an infectious cDNA clone of the Thailand classical PEDV strain AVCT12 into a bacterial artificial chromosome (BAC) using eight contiguous cDNA fragments (Jengarn et al, 2015).…”
Section: Introductionmentioning
confidence: 99%